The influence of reagents ball milling on the lithium ferrite formation; Journal of Thermal Analysis and Calorimetry; Vol. 138, iss. 3 - Lysenko E. N. Elena Nikolaevna; Nikolaev E. V. Evgeny Vladimirovich; Surzhikov A. P. Anatoly Petrovich; Nikolaeva S. A. Svetlana Andreevna; Plotnikova I. V. Inna Vasilievna (2019, 2019)
Title screen